Fibroblasts: Immunomodulatory factors in refractory diabetic wound healing - Liu, Ye; Liu, Yiqiu; He, Wenjie; Mu, Xingrui; Wu, Xingqian; Deng, Junyu; Nie, Xuqiang (Frontiers in Immunology, 2022)
Diabetes is a systemic disease in which patients with diabetes may develop peripheral neuropathy of the lower extremities and peripheral vascular disease due to long-term continuous exposure to high glucose. Diabetic wound healing dysfunction due to inadequate insulin secretion (type 1) or underuse (type 2) has been associated with high glucose toxicity. Chronic nonunion of diabetic wounds is one of the major complications of diabetes. When the condition worsens, it can cause amputation or even death of patients, which seriously affects their quality of life. In general, the delayed healing of diabetes wound is due to the lack of chemokines, abnormal inflammatory response, lack of angiogenesis and epithelial formation, and fibroblast dysfunction. The incidence of several chronic debilitating conditions is increasing in patients with diabetes, such as chronic renal insufficiency, heart failure, and hepatic insufficiency. Fibrosis is an inappropriate deposition of extracellular matrix (ECM) proteins. It is common in diabetic patients causing organ dysfunction. Fibrosis is an inappropriate deposition of extracellular matrix (ECM) proteins. It is common in diabetic patients causing organ dysfunction. The fibrotic mechanism of diabetic fibroblasts may involve direct activation of permanent fibroblasts. It may also involve the degeneration of fibers after hyperglycemia stimulates immune cells, vascular cells, or organ-specific parenchymal cells. Numerous studies confirm that fibroblasts play an essential role in treating diabetes and its complications. The primary function of fibroblasts in wound healing is to construct and reshape the ECM. Nowadays, with the widespread use of single cell RNA sequencing (scRNA-seq), an increasing number of studies have found that fibroblasts have become the critical immune sentinel cells, which can detect not only the activation and regulation of immune response but also the molecular pattern related to the injury. By exploring the heterogeneity and functional changes of fibroblasts in diabetes, the manuscript discusses that fibroblasts may be used as immunomodulatory factors in refractory diabetic wound healing, providing new ideas for the treatment of refractory diabetic wound healing.